Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let be the following sequence $x_{n}$, $n\geq0$, $0<x_{0}<1$ that satisfies the following recurrence: $$ x_{n+1}=x_{n}-x_{n}^2+x_{n}^3-x_{n}^4+x_{n}^5-x_{n}^6$$

Having given this, i'm required to calculate: $$\lim_{n\rightarrow\infty} n x_{n} $$

share|cite|improve this question
up vote 3 down vote accepted

The recurrence yields $$ \frac{x_{n+1} }{x_n} = (1-x_n) (1+x_n^2 + x_n^4) .$$

For $z\in (0,1)$ we have $ 0< (1-z)(1+z^2+z^4) < 1$ so $x_n$ is montonically decreasing and non-negative. Also note that since $x_n$ is a non-negative sequence we have $0\leq x_n \leq 1$ for all $n\in \mathbb{N}$ (for if $x_k>1$ then $x_{k+1}<0$). Thus $x_n\to x$ where $x\in[0,1].$ It must satisfy $$x=x(1-x)(1+x^2+x^4)$$ which can be written $$ x\left((1-x)(1+x^2+x^4) -1\right)=0.$$ Thus $\displaystyle \lim_{n\to \infty} x_n=0$ and consequentially, $\displaystyle \lim_{n\to\infty} \frac{x_{n+1}}{x_n} = 1.$

Now we calculate $$ \frac{(n+1) - n}{\frac{1}{x_{n+1}} - \frac{1}{x_n} }= \frac{x_{n+1} x_n}{x_n - x_{n+1}}= \frac{x_{n+1}x_n}{x_n^2-x_n^3 +x_n^4 -x_n^5 +x_n^6} $$

$$= \frac{x_{n+1}/x_n }{1-x_n +x_n^2 - x_n^3 + x_n^4}\to 1.$$

Hence, by the Stolz–Cesàro theorem we conclude $\displaystyle \lim_{n\to\infty} nx_n =1.$

share|cite|improve this answer
    
great solution! Thanks. – user 1618033 Jun 2 '12 at 14:40

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.